Dimensions of Ecological Discourse – Overview of Problems and Selected Literature - Zacher, Lech W. (Problemy Ekorozwoju, 2011)
In the last few decades the ecological (environmental or sustainability) discourse has been advanced and intensified. This discourse takes its place predominantly in highly developed countries and also in forums of international organizations and institutions (e.g. UN, Greenpeace, alter-globalist movements). There is more and more dimensions of research and discussions. New ideas, concepts, theoretical approaches, methodologies, also practical innovations and procedures are emerging. The discourse is to a growing extent multi- and interdisciplinary, not excluding however other perspectives like e.g. technological, economic, political, managerial, ethical. Important areas of studies and debates are such as government policies, business strategies, behavior of citizens, not to mention the global dimension of the problematique.